Primární volvulus tenkého střeva u mladého nemocného - Pastor, J; Adámek, S; Polanecký, O (Rozhledy v chirurgii, 2014)
The authors present a rare case of a young male patient with primary small bowel volvulus. They show the main points to be considered in clinical diagnosis of this kind of acute abdomen and the importance of CT scan in such cases.
Keywords: volvulus intestini; mladý dospělý; Humans; lidé; Male; Young Adult; počítačová rentgenová tomografie; Tomography, X-Ray Computed; tenké střevo; Intestinal Volvulus; mužské pohlaví; Intestine, Small